Influence of extrusion and ECAP processes on mechanical, tribological and corrosion properties of biodegradable Zn1AgCuMg alloy - Sezek, Sinan; Aksakal, Bunyamin (Springer France, 2025)
Zn-based alloys have attracted significant attention as potential candidates for biodegradable implants due to their excellent biocompatibility; however, their inherently low tribological performance continues to restrict practical applications. In the present study, a Zn1AgCuMg alloy was fabricated via induction melting-casting and subsequently processed through cold extrusion and equal channel angular pressing (ECAP) using various routes (A, C, R, Bc) and pass numbers (1-4). The processing resulted in substantial microstructural refinement, reducing the average grain size from 245 mu m in the as-cast condition to 72 mu m after ECAP Route-Bc with four passes, accompanied by an increase in hardness from 62 HV to 113 HV. The yield strength improved from 150 MPa (as-cast) to 164 MPa after extrusion, and further to 217 MPa following ECAP Route-Bc (four passes). Similarly, the corrosion rate decreased from 294 mpy in the untreated alloy to 232 mpy after extrusion and to 66.16 mpy after ECAP Route-Bc (four passes). Tribological assessment revealed negligible differences between extrusion and 1-2 pass ECAP samples; however, a marked enhancement in wear resistance was observed in the 3-4 pass ECAP conditions, with the lowest friction coefficient (0.083) achieved for ECAP Route-Bc (four passes). These results confirm that controlled severe plastic deformation via ECAP can concurrently improve mechanical strength, wear resistance, and corrosion resistance in Zn-based biodegradable alloys, with multi-pass ECAP Route-Bc offering the most balanced performance for prospective implant applications.
Keywords: Extrusion; ECAP; Wear; Corrosion; Biodegradable alloy processing